Does Country of Origin Matter? Exploring Its Effect on Purchase Decisions Mediated by Perceived Quality - Mulyaningsih, Hendrati Dwi; Sufian, Muhammad Fathoni; Saraswati, Nindya (Indonesian Journal of Social Research (IJSR), 2025)
This research explores whether a product’s country of origin (COO) influences consumer purchasing decisions through the mediating role of perceived quality. The study is grounded in consumer behavior and brand perception theories, focusing on Adidas users in Bandung as a case. Using a quantitative method and Structural Equation Modeling (SEM) via SmartPLS, data were collected from 110 respondents through a structured questionnaire. The analysis confirmed that COO has a significant positive influence on perceived quality and, subsequently, on purchase decisions. However, the COO does not directly influence purchasing decisions without the mediation of perceived quality. These findings highlight the importance of perceived product quality in bridging the consumer's perception of a brand's origin and purchasing behavior. This study contributes to marketing and branding strategies by emphasizing the need for companies to enhance the perceived quality of their products when leveraging their country of origin in brand positioning.